2007
DOI: 10.1159/000111501
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide and the mTOR Inhibitor RAD001 (Everolimus) Block Proliferation and Interact with the Akt-mTOR-p70S6K Pathway in a Neuro-Endocrine Tumour Cell Line

Abstract: Background/Aim: The mode of action of the somatostatin analog octreotide on neuro-endocrine tumour proliferation is largely unknown. Overexpression of the proto-oncogene Akt/PKB (protein kinase B) has been demonstrated in certain neuro-endocrine tumours: Akt activates downstream proteins including mTOR and p70S6K, which play an important role in cell proliferation. RAD001 (everolimus) is a novel agent that is being trialled in the treatment of neuro-endocrine tumours, and is known to interact with mTOR. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 144 publications
8
75
0
4
Order By: Relevance
“…This might be due to an induction of growth arrest in G 0 /G 1 phase and enhanced apoptosis (Zitzmann et al 2007). Furthermore, it has been proposed that deactivation of the AKT-mTOR kinase axis is responsible for this effect (Grozinsky-Glasberg et al 2008). These in vitro results are in line with our findings that mTOR expression as well as downstream activation of 4EBP1, eIF4E and S6K correlates with proliferation in GEP-NET.…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to an induction of growth arrest in G 0 /G 1 phase and enhanced apoptosis (Zitzmann et al 2007). Furthermore, it has been proposed that deactivation of the AKT-mTOR kinase axis is responsible for this effect (Grozinsky-Glasberg et al 2008). These in vitro results are in line with our findings that mTOR expression as well as downstream activation of 4EBP1, eIF4E and S6K correlates with proliferation in GEP-NET.…”
Section: Discussionsupporting
confidence: 90%
“…In this study Zitzmann and coworkers (Zitzmann et al 2007) observed that treatment with everolimus led to inhibition of cell growth by G0/G1 cell cycle arrest and promotion of apoptosis. Similarly, this antiproliferative effect was observed in INS1 cells, a rat insulinoma cell line, where everolimus inhibited phosphorylation of both mTOR and its downstream target S6K1 (Grozinsky-Glasberg et al 2008).…”
Section: Tk Receptor Growth Factorsmentioning
confidence: 62%
“…So far, only a few preclinical reports, mainly based on in vitro experiments, have appeared. [5][6][7][8] In this context, the objective of our study was to evaluate, in vitro and in vivo, the effects of rapamycin on intestinal endocrine tumor cell lines, representative of the human highgrade endocrine carcinomas that are putative targets for treatment by rapamycin analogues. 19 Our results suggest that rapamycin may act through several coordinated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Only four recent works reported on the effects of rapamycin or its analog RAD001 on endocrine cell lines on the basis of in vitro experiments. [5][6][7][8] To gain further insight into the mechanisms of antitumor activity of rapalogues in GEP neuroendocrine tumors, we designed an experimental study based on two murine endocrine cell lines, STC-1 and GLUTag, which mimic the behavior of human high-grade endocrine carcinoma. After establishing the in vitro effects of rapamycin, we attempted to evaluate in vivo, using a preclinical animal model of intrahepatic dissemination developed in the laboratory, 9 the relative contributions of the antiproliferative, proapoptotic, and antiangiogenic effects that may be exerted by rapamycin alone or in combination with the PI3K inhibitor LY294002, which targets the same pathway.…”
mentioning
confidence: 99%